Eskimos Know Best - Carlson, William S. (William Samuel) (Tufts Archival Research Center, 2006)
William Carlson, president of the State University of New York, describes how his experience of living with an Inuit family in Greenland disproved his belief of belonging to a superior race, and states his beliefs in the brotherhood of humanity, the virtue of patience, the need of self-evaluation, the unity of family, and the method of science. Contains a short advertisement for This I Believe book (this essay included in the book).